A global perspective of bioaccumulation research using bibliometric analysis. Issue 2 (3rd July 2018) - Lei, Jing; Fu, Hui-Zhen; Ho, Yuh-Shan
Abstract : Contaminant bioaccumulation has long been used as a key indicator of the potential risk and toxic effects of contaminants to the environment and human health. In the present study, a bibliometric analysis based on the Science Citation Index Expanded from Thomson Reuters' Web of Science Core Collection was carried out to gain insights into research activities and tendencies of global bioaccumulation from 1991 to 2014. Study emphases included performance of annual outputs, countries, institutions, Web of Science categories, journals, research hotspots, and articles with lasting impacts. Results indicated that annual outputs of the bioaccumulation articles increased steadily in 1991 to 2014. USA dominated the bioaccumulation field, followed by China, Canada, and France. Government agencies, such as Environment Canada and the US Environmental Protection Agency were the leading institutions in bioaccumulation research. The most prolific and promising category was environmental science, which was significantly ahead of other categories, such as toxicology, marine and freshwater biology, as well as environmental engineering. The bioaccumulation articles were dispersed in 1, 267 journals, whereas half of the articles reside on 19 core journals. Research focuses and hot issues in the bioaccumulation field were evaluated by word cluster analysis. Toxic effects, exposure, risk analysis and/or assessment, as well as bioavailability of chemicals, are major concerns in the bioaccumulation field. Metals, such as mercury, cadmium, copper, lead, and arsenic, were contaminants of greatest concern, among which mercury was the most studied. Persistent organic pollutants, such as polychlorinated biphenyl, polycyclic aromatic hydrocarbons, and organochlorine compounds, were also very significant in the study of bioaccumulation. Substances with lasting impact were evaluated by citation lives of top articles. Perfluorooctane sulfonate and methylmercury have lasting impacts for their unusual routes in bioaccumulation. Moreover, methodological innovations in acquiring food chain position with stable nitrogen isotopes played an important role in bioaccumulation research.